Expression of ALG3 in Hepatocellular Carcinoma and Its Clinical Implication - Zhao, Zhen; Zheng, Zehao; Huang, Jianfeng; Wang, Jianxi; Peng, Tianyi; Lin, Ye; Jian, Zhixiang (Frontiers in Molecular Biosciences, 2022)
Background: Recent studies have shown that Alpha-1,3-mannosyltransferase (ALG3) promoted tumorigenesis and progression in multiple cancer types. Our study planned to explore clinical implication and potential function of ALG3 in hepatocellular carcinoma. Materials and Methods: Data from public databases were used to analyze ALG3 expression and its impact on clinical significance of patients with HCC. ALG3 expression was confirmed by qRT-PCR and western blot. Immunohistochemistry was used to confirm ALG3 expression and explore its clinical implication in HCC. KEGG, GO and GSEA enrichment analysis were utilized to explore the biological pathways relation to ALG3 in HCC. TIMER2.0 was applied to assess the association between ALG3 and Immune Infiltration. Results: qRT-PCR, WB and IHC proved ALG3 was highly overexpressed in HCC tissues. The Kaplan Meier analysis verified the overexpression of ALG3 was related with poor overall survival (P<0.001). Multivariate cox regression analysis showed that high ALG3 expression was an independent risk prognostic factor. GSEA and TIMER2.0 predicted that ALG3 participates in cell differentiation, cycle and correlates to immune cell infiltration. Conclusion: ALG3 was overexpressed and considered as a potential indicator of survival in HCC and our findings provided a novel therapeutic target for HCC.